2016
DOI: 10.1007/s00449-016-1653-2
|View full text |Cite
|
Sign up to set email alerts
|

Using a flexible shaft agitator to enhance the rheology of a complex fungal fermentation culture

Abstract: The rheology behavior of biological fluids particularly when the viscosity is high and rheology is complex, is an important issue to understand, particularly for studies in mass-transfer and for solving technical problems with mixing in stirred bioreactors. In this paper, the use of a Swingstir(®) impeller during the fermentation of Aspergillus oryzae resulted in decreases from the parameters of a power-law model, in viscosity and in the thixotropic behavior of a cultivation broth. The results showed that both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Without the use of support particles, however, K was increased, from the first sampling to the end of the fermentation. Previous studies have shown that increasing the broth viscosity makes cultivation a challenge [13], [17]. These results show that utilizing large BSPs could be an easy solution to decreasing the non-Newtonian properties and preventing the obstacles that arise from a high-viscosity cell culture.…”
Section: Studying the Rheology Of An Immobilized Submerged Culturementioning
confidence: 66%
See 3 more Smart Citations
“…Without the use of support particles, however, K was increased, from the first sampling to the end of the fermentation. Previous studies have shown that increasing the broth viscosity makes cultivation a challenge [13], [17]. These results show that utilizing large BSPs could be an easy solution to decreasing the non-Newtonian properties and preventing the obstacles that arise from a high-viscosity cell culture.…”
Section: Studying the Rheology Of An Immobilized Submerged Culturementioning
confidence: 66%
“…In the culture containing small particles, the main reason for the loss of the immobilized cells was the structure of the particles. According to previous publications, [13] the average pellet size of the small-particle cells at 72 h was approximately 6.5 mm and the small pellets could not stably adhere with such a small surface area (3*6 or 3*3 ). The decrease in the culture when using 1,000large BSPs was obviously neither the number of particles nor the structure, which suggests more study on morphology is needed in the near future to determine the reason.…”
Section: A Effect That the Size And Number Of Biomass Support Particmentioning
confidence: 76%
See 2 more Smart Citations
“…Besides the attempt to avoid, e.g., high values of shear stress responsible for the disintegration of microorganisms, by geometrical adjustments of the impeller, one approach considering the potentially changing rheological behavior of the cultivation broth during the fermentation time is using flexible parts in the stirring system. Ghobadi et al , applied the Swingstir® impeller (SS) in their fungus cultivation experiments and compared its performance with a Fullzone® impeller (FZ; large impeller covering the whole filling height just at the lower limit of the near‐wall d / D value) and two 6‐SBDTs in a multistage arrangement. The SS is an off‐center stirrer with a flexible shaft moving concentrically above the aerator.…”
Section: Impellers Used In Cultivation Systemsmentioning
confidence: 99%